Big brother’s help: the dynamics of the Indonesian narrative of China’s role in Indonesian development - Hikmatul Akbar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A narrative is a story someone tells to influence the person they are talking to, the discussion community, or society. The information narrative carries may or may not be valid. Narratives about China developed abundantly in Indonesia during the Jokowi administration. The rise and fall in narrative frequency are greatly influenced by political activities in Indonesia, public perception, and China’s relations with Indonesia. While many narratives come from false information or hoaxes, many positive narratives about China come from valid data. Positive narratives about China’s economic assistance, China’s position as a leading country, and the influence of Chinese culture can overcome the dominance of negative narratives on social media about China and the Jokowi government, many of which originate from hoaxes. Public perception and approval of Jokowi’s government confirm that the narrative about China’s assistance to Indonesia is well-assented